G346 Paediatric ECG interpretation and documentation in a Children's Emergency Department – a service evaluation and action plan. (7th April 2014) - Venugopalan, P; Bevan, C; Krishnan, S; Davies, H
Abstract : Aims: To review the practice, usefulness and interpretation of electrocardiogram (ECG) in a Children's Emergency Department (CED), following a clinical risk incident due to the lack of formal review process of all ECGs in the CED. Methods: All ECGs performed in the CED (25, 000 annual attendances) over a 4-month period were analysed retrospectively. Data collected included a) patient data recorded on the ECG printout (name, date of birth, hospital number), b) automatic machine report on the ECG printout, c) interpretation of the ECG by the attending physician, and d) documentation of the results in the case notes. Results: 71 ECGs were performed during the study period. Eight cases were excluded. The 63 patients (M: F 1:1.5) were further analysed. Ages ranged from 21 days to 16 years (mean 10.6yrs). The main indications for the test were chest pain (33%), syncope (32%), seizure or life threatening event (15%), drug overdose (10%) and miscellaneous (10%). The automatic reporting system on the ECG machine identified 15 (23%) ECGs as showing a prolonged corrected QT interval (QTc). Manual measurement and computation (Bazet's formula) however, showed all these records have a normal QTc. There were 9 (2%) abnormal ECGs, which included supraventricular tachycardia (1), left axis deviation (2), left ventricular hypertrophy by voltage criteria (3), left bundle branch block (1), right bundle branch block (1), ST elevation (1). Conclusion: The study showed widespread deficiencies in the performing, interpretation and documentation of ECGs in the CED. A guideline for interpretation of ECG has been introduced and a proforma designed to guide a detailed reporting of all ECGs. There is now a process for a formal review of all ECGs performed in the department which will prevent any unnecessary cardiology referral and prevent any abnormal ECGs being missed.